2013
DOI: 10.1002/adhm.201200368
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cellulose Nanofibrillar Patch as a Wound Healing Platform of Tympanic Membrane Perforation

Abstract: Bacterial cellulose (BC)-based biomaterials on medical device platforms have gained significant interest for tissue-engineered scaffolds or engraftment materials in regenerative medicine. In particular, BC has an ultrafine and highly pure nanofibril network structure and can be used as an efficient wound-healing platform since cell migration into a wound site is strongly meditated by the structural properties of the extracellular matrix. Here, the fabrication of a nanofibrillar patch by using BC and its applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 23 publications
2
41
0
3
Order By: Relevance
“…The experimental study on rats lasted 12 weeks. This experiment confirmed that after this time the functions of the tympanic membrane were recovered faster than in the classical method and the tympanic membrane healed more quickly in the presence of the BNC materials …”
Section: Bacterial Nanocellulose In Traumatic Tympanic Membrane Perfosupporting
confidence: 77%
“…The experimental study on rats lasted 12 weeks. This experiment confirmed that after this time the functions of the tympanic membrane were recovered faster than in the classical method and the tympanic membrane healed more quickly in the presence of the BNC materials …”
Section: Bacterial Nanocellulose In Traumatic Tympanic Membrane Perfosupporting
confidence: 77%
“…Recently, Kim et al (2013) reported the fabrication of a nanofibrillar patch by using BC as a wound-healing scaffold for TM perforation. BC is endowed with the expected properties of an ideal material for traumatic eardrum perforation repair: a nanostructured surface, biocompatibility, transparency, and appropriate mechanical.…”
Section: Tympanic Membranementioning
confidence: 99%
“…Silk fibroin and bacterial cellulose are two biological materials widely utilized in scaffold fabrication and tissue engineering (Kim et al, 2013;Tu et al, 2013). We fabricated the composite scaffold of SF and BC to synergize the strength of SF with the elasticity and water absorption properties of BC (Zhu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Silk fibroin (SF)-based scaffolds have been widely utilized in bone repair, bladder regeneration and wound healing due to its good biocompatibility, mechanical properties, high plasticity and biodegradability (Tu et al, 2013). Bacterial cellulose (BC) is produced by certain types of bacteria and is characterized by good biocompatibility, high tensile strength, porosity, strong water absorption, making it suitable for tissue engineering of bone and nerve, repair of tympanic membrane perforation and vascular grafts (Gu et al, 2014;Kim et al, 2013). Recently, we have fabricated a composite scaffold of SF and BC that combined the mechanical strength of SF and water absorption properties of BC (Zhu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%